Card game as a pedagogical tool for numeracy skills development - Parmjit Singh; Teoh Sian Hoon; Akmal Md Nasir; Adlan Md Ramly; Syazwani Md Rasid; Chew Cheng Meng (International Journal of Evaluation and Research in Education (IJERE), 2021)
Given the hypothesis that card games form a strong tool capable of shaping the aforementioned interest, this study has developed a card game called Math Zap as a pedagogical tool for numeracy skills development in the context of mental computation. It is geared towards investigating the efficacy of this Math Zap card game, in facilitating the development of numeracy skills amongst learners, and their attitude towards using it as a pedagogical tool. A mix method approach using an experimental and descriptive design was taken and tested amongst 34 primary school students aged 12 to 13. From the results of the study, it is found that the Math Zap card game is a highly effective learning tool in so far as the enhancement of students’ numeracy computation skills in the areas of fractions, percentages and decimals are concerned. This is evidenced by a statistical significant pre-post test score increment. Furthermore, students were rather positive and receptive towards the game, further substantiating the claim of it being a useful pedagogical tool.